Targeted Prostate Gland Biopsy With Combined Transrectal Ultrasound, mpMRI, and 18F-FMAU PET/CT. (August 2015) - Jadvar, Hossein; Chen, Kai; Ukimura, Osamu
Abstract : Abstract: We report on a 61-year-old man with elevated serum prostate-specific antigen level of 10.5 ng/mL who had undergone prior negative standard transrectal ultrasound biopsy at another institution. He was referred to our medical center for evaluation and underwent a clinical 3-T multiparametric MRI and a research protocol PET/CT with the cellular proliferation radiotracer 18 F-FMAU (2′-deoxy-2′-[ 18 F]fluoro-5-methyl-1-β-D-arabinofuranosyluracil). The PET/CT and multiparametric MRI were fused with transrectal ultrasound images for real-time hybrid image–based targeting of the biopsy needle. PET/CT with 18 F-FMAU was helpful in localizing the nonstandard biopsy sites that on histopathology revealed suspected tumor deposits.